A protein-trap allele reveals roles for Drosophila ATF4 in photoreceptor degeneration, oogenesis and wing development - Deepika Vasudevan; Hidetaka Katow; Huai-Wei Huang; Grace Tang; Hyung Don Ryoo (Disease Models & Mechanisms, 2022)
Metazoans have evolved various quality control mechanisms to cope with cellular stress inflicted by external and physiological conditions. ATF4 is a major effector of the integrated stress response, an evolutionarily conserved pathway that mediates adaptation to various cellular stressors. Loss of function of Drosophila ATF4, encoded by the gene cryptocephal (crc), results in lethality during pupal development. The roles of crc in Drosophila disease models and in adult tissue homeostasis thus remain poorly understood. Here, we report that a protein-trap Minos-mediated integration cassette insertion in the crc locus generates a Crc-GFP fusion protein that allows visualization of Crc activity in vivo. This allele also acts as a hypomorphic mutant that uncovers previously unknown roles for crc. Specifically, the crc protein-trap line shows Crc-GFP induction in a Drosophila model for retinitis pigmentosa. This crc allele renders flies more vulnerable to amino acid deprivation and age-dependent retinal degeneration. These mutants also show defects in wing veins and oocyte maturation. Together, our data reveal previously unknown roles for crc in development, cellular homeostasis and photoreceptor survival. This article has an associated First Person interview with the first author of the paper.